The Economic Value of Resources Romokalisari Advanture Land Ecotourism in the Sub-district, Benowo, Surabaya City, East Java - Rhochmad Wahyu Illahi; Tajuddin Noor Noor; Alberta Esti H; Exist Saraswati; Choirunnisa Nur Prajasti; Rachintha Fica Novita Sari (Grouper, 2024)
Regarding fisheries in Indonesia, there is a need for balanced management so that existing resources can be used and utilized optimally. The Romokalisari Adventure Land tourist attraction, located in Benowo District, Surabaya City, is a tourist attraction that utilizes the balance between the two natural resources in the form of land and sea. The method used to find the economic value of resources in Romokalisari Adventure Land Ecotourism is a simple method, where there is a regression model to determine the influence of each factor and the Travel Cost Method (TCM) travel cost model to determine the economic value of resources. The results of this research show that the actual income obtained by Romokalisari Adventure Land Ecotourism is IDR. 120,000,000,- / year and potential income of IDR 720,000,000,-/ year. Potential income can also be generated by the emergence of potential that appears as an activity sector to expand economic income.